Systemic Therapy for Metastatic Colon Cancer: New Frontiers - Pumpalova, Yoanna S. (Clinics in Colon and Rectal Surgery, 2024)
We have made steady gains in improving overall survival in patients with metastatic, unresectable, colon cancer in the last 5 to 10 years. The backbone of systemic treatment for most patients remains combination chemotherapy, but the field is becoming increasingly biomarker driven, with exciting new targeted therapies on the horizon. This review is organized in sections corresponding to currently relevant biomarkers in colon cancer and will summarize first-, second-, and third-line standard of care for metastatic, unresectable, colon cancer. The last section is intended to introduce the reader to promising agents and novel therapeutic strategies currently under investigation.
Keywords: metastatic colon cancer; systemic therapy; investigational agents